Studi eksplorasi nilai-nilai Serat Wulang Putri Nyi Adisara: respon pembaca perempuan jawa masa kini - Pramitasari, Dewi Ajeng; Widagdo, Sungging (Aksara: Jurnal Bahasa dan Sastra, 2024)
Serat Wulang Putri Nyi Adisara is a classic text that provides guidance on becoming an ideal Javanese woman. This study examines contemporary Javanese women's perceptions of the traditional values outlined in Serat Wulang Putri Nyi Adisara. The method used is a descriptive qualitative survey and a literary reception approach towards the views of female readers of the Javanese Literature Study Program and Javanese Language and Literature Education Study Program, FBS Unnes. Through a literary reception approach to the reader's view of Serat Wulang Putri Nyi Adisara, the interaction between traditional hopes and the reader's modern aspirations is explained. The findings in this research reveal an understanding of the values of Serat Wulang Putri Nyi Adisara among contemporary Javanese women. In Serat Wulang Putri Nyi Adisara women are taught to be patient, sincere, and obedient. This study contributes to a broader understanding of how these texts shape roles and how these roles evolve over time in response to social and cultural change.Keywords: Serat Piwulang, Nyi Adisara, woman, reception, literature